2015
DOI: 10.1186/s12889-015-2380-3
|View full text |Cite
|
Sign up to set email alerts
|

The REFANI Pakistan study—a cluster randomised controlled trial of the effectiveness and cost-effectiveness of cash-based transfer programmes on child nutrition status: study protocol

Abstract: BackgroundCash-based transfer programmes are an emerging strategy in the prevention of wasting in children, especially targeted at vulnerable households during periods of food insecurity or during emergencies. However, the evidence surrounding the use of either cash or voucher transfer programmes in the humanitarian context and on nutritional outcomes is elusive. More evidence is needed not only to inform the global community of practice on best practices in humanitarian settings, but also to help strengthen n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…In the abovementioned study in Pakistan, a reduced prevalence of acute malnutrition was observed only in the arm receiving double the amount of money that the standard CBI recipient received (US$28.00 versus US$14.00 per month); the amounts were designed to cover 20% and 10% of the energy requirements of a typical household, respectively [ 16 ]. However, in our study the cash transfer was designed to cover 100% of the energy requirements of the typical household [ 20 ], but despite this relatively larger transfer, we observed no associated impact on nutritional status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the abovementioned study in Pakistan, a reduced prevalence of acute malnutrition was observed only in the arm receiving double the amount of money that the standard CBI recipient received (US$28.00 versus US$14.00 per month); the amounts were designed to cover 20% and 10% of the energy requirements of a typical household, respectively [ 16 ]. However, in our study the cash transfer was designed to cover 100% of the energy requirements of the typical household [ 20 ], but despite this relatively larger transfer, we observed no associated impact on nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…Conducted by the Research on Food Assistance for Nutritional Impact (REFANI) consortium, the REFANI–Somalia study is 1 of 3 studies—the other 2 being in Niger and Pakistan [ 16 , 17 ]—that seek to contribute to the evidence base regarding the nutritional impact of humanitarian CBIs. Using a non-randomised cluster design, this study aimed to assess whether a CBI, allocated to beneficiaries following a vulnerability assessment, would improve child dietary diversity and reduce acute malnutrition risk in children aged 6–59 months living in IDP camps near Mogadishu, Somalia.…”
Section: Introductionmentioning
confidence: 99%
“…The trial design, setting, and characteristics of the study population have been previously described [16]. …”
Section: Methodsmentioning
confidence: 99%
“…While more data on cash transfers are needed in specific regions, such as sub‐Saharan Africa, a growing quantity of evidence indicates that cash transfers may improve nutritional outcomes by increasing food supply, money spent on groceries and quality of food consumed . Two ongoing studies aim to assess impacts of cash transfer specifically on paediatric populations in emergency settings .…”
Section: Discussionmentioning
confidence: 99%